2019
DOI: 10.1021/acsnano.9b02858
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Nanophotonics: Robust and Soft Random Lasers

Abstract: Self-healing technology promises a generation of innovation in cross-cutting subjects ranging from electronic skins, to wearable electronics, to point-of-care biomedical sensing modules. Recently, scientists have successfully pulled off significant advances in self-healing components including sensors, energy devices, transistors, and even integrated circuits. Lasers, one of the most important light sources, integrated with autonomous self-healability should be endowed with more functionalities and opportuniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Self-healing materials are widely used in military equipment, electronic products, [14][15][16][17][18][19] automobiles, airplanes, [20][21][22] building materials, [23] biological materials, [24] medical materials [25][26][27][28][29] and biomimetic technology, [30,31] The proportion of application is also increasing with each passing year (Figs. 1 a, b and c), for instance, self-healing materials can be used in dentistry in medical field.…”
Section: Introductionmentioning
confidence: 99%
“…Self-healing materials are widely used in military equipment, electronic products, [14][15][16][17][18][19] automobiles, airplanes, [20][21][22] building materials, [23] biological materials, [24] medical materials [25][26][27][28][29] and biomimetic technology, [30,31] The proportion of application is also increasing with each passing year (Figs. 1 a, b and c), for instance, self-healing materials can be used in dentistry in medical field.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the present interdisciplinary technological standards, stretchable electronics have shot their way up when it comes to the demand in the electronics market . The random lasers are no longer aloof, and researchers have been working toward fabricating stretchable, wearable, and flexible random lasing systems . Hu et al .…”
Section: Introductionmentioning
confidence: 99%
“…36 The random lasers are no longer aloof, and researchers have been working toward fabricating stretchable, wearable, and flexible random lasing systems. 37 Hu et al 38 have demonstrated a wrinkled system assisting random lasing action where semiconductor quantum dots were employed as gain media. There is not even a single report where UCNPs have been subjected to flexible and stretchable systems, thereby exhibiting random lasing as a whole.…”
Section: ■ Introductionmentioning
confidence: 99%
“…51,52 Great efforts have been made for the development of polymeric materials based on reversible covalent bonds or supramolecular interaction, and these healable polymeric materials have been successfully employed in the construction of healable nanocomposite materials for use as electronic devices. [53][54][55][56][57] Recently, structural color nanocomposites with healable capability have also been obtained with healable polymeric materials, and it has been shown that the introduction of the healable polymeric materials can effectively ensure the reliability and the longterm use of the PCs after severe damage. Furthermore,…”
Section: Introductionmentioning
confidence: 99%